Multitude : between innovation and negation. - Virno, Paolo; Bertoletti, Isabella; Cascaito, James; Casson, Andrea (Los Angeles : Semiotext(e), 2008)
Part 1: So-called "evil" and criticism of the state## Part 2: Jokes and innovative action: for a logic of change##Part 3: Mirror neurons, linguistic negation, reciprocal recognition.
boek